Woman, Authority and Manifestation of God in The Narrative of Sufism - khotimah , Khusnul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This study aims to analyze the position of women in Islamic spiritual discourse. During this time, patriarchal culture places women in subordinate men in a variety of situations; politics, economics, culture, education and religion. This study criticizes the results of studies that narrate that women are second class. Through qualitative methods and descriptive analysis, this study relies on primary documents about traces of women in the labyrinth of Sufism. The results of the study indicate that the position of women is so central and a bridge to climb the title of Insan Kamil (perfect human). Many minor, nagging, and wrong views that view women has tempting, wild, bad instinct and as a barrier for the Sufis to reach the highest level. In the context of Sufism, women as seducers are God's elements that manifest on humans. As long as directed, she is the road to the perfection and the maqam of Insan Kamil. The world of Sufism understands women in the corridors of harmony and duality. Women are miniatures of nature. The famous Ibn ‘Arabi thesis says that God wants to be known so He creates nature. There is duality in it, Qahar, Luthf, Jamal and also Jalal. To the way of God, it cannot be separated from feminine and masculine aspects. Recognizing women is like recognizing God.